2022
DOI: 10.3389/fnut.2022.865991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volatile Profile and In Vitro Antioxidant Activity of Fermented Green Tea Infusion With Pleurotus sajor-caju (Oyster Mushroom)

Abstract: Green tea has distinct astringency, bitter taste, and typical green flavor because of its post-harvest treatment without withering and enzymatic oxidation. Microbial fermentation has been identified as a promising strategy that could give green tea infusion a special taste flavor. This might be linked to the metabolic transformation ability of microorganisms. In this study, starter culture of edible mushroom Pleurotus sajor-caju (oyster mushroom) was used for submerged fermentation of green tea infusion in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…bruxellensis, in monoculture, produced the highest concentrations of the benzenoids 4-ethylphenol and methyl salicylate, while single Z. parabailii was the biggest producer of the sulfur-containing compounds dimethyl sulfide and methionol, and benzaldehyde. Methyl salicylate (spicy, wintergreen) and benzaldehyde (cherry, almond), as linalool and β-citronellol, are mainly released from bound glycosides in fermented beverages by yeast-derived glycosidase enzymes, and they are all important contributors to the flavor of tea [56,57]. Brettanomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…bruxellensis, in monoculture, produced the highest concentrations of the benzenoids 4-ethylphenol and methyl salicylate, while single Z. parabailii was the biggest producer of the sulfur-containing compounds dimethyl sulfide and methionol, and benzaldehyde. Methyl salicylate (spicy, wintergreen) and benzaldehyde (cherry, almond), as linalool and β-citronellol, are mainly released from bound glycosides in fermented beverages by yeast-derived glycosidase enzymes, and they are all important contributors to the flavor of tea [56,57]. Brettanomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Linalool has a citrus-like and flowery aroma [27,41]. Su et al [42] showed that linalool is the key volatile compound of green tea and that it plays an important role in the aroma of green tea. Nonanal is widely found in green tea and has a sweet, fruity flavor [37].…”
Section: Key Aroma Compounds Identified By Oav In the Eg Groupmentioning
confidence: 99%
“…Anthocyanins and catechins are important flavonoid compounds in fresh tea leaves. The purple shoots of tea plants contain too many anthocyanins, resulting in greater bitterness and astringency (Lai et al, 2016; Su et al, 2022). Anthocyanins and catechins are derived from the phenylpropanoid and flavonoid biosynthetic pathways involving complex enzyme‐catalysed reactions primarily regulated by the phenylalanine metabolic pathway (Mei et al, 2021; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%